2018
DOI: 10.18805/lr-3849
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and combining ability studies for economic traits in garden pea (Pisum sativum L.)

Abstract: A line × tester analysis comprising of 7 promising lines and three testers having wider genetic base was carried out for pod yield and related horticultural traits in garden pea (Pisum sativum L.) Among parents, line 17, line 14 and Palam Triloki were observed as best general combiners for pod yield and majority of component traits. Cross, line 17 x Arkel showed high heterosis and SCA effects for pod yield and related horticultural traits. The cross combination line 17 x Palam Triloki was most promising for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
(4 reference statements)
3
3
0
Order By: Relevance
“…Previously, Rebika (2017) also observed heterobeltiosis and standard heterosis for seed yield along with most of its yield components in pea which have the immense potential to exploit hybrid vigour or to isolate desirable segregants. Similar findings in pea have been reported by Nageshwar et al (2020), Katoch et al (2019), Halil et al (2019 and Kumari et al (2015).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Previously, Rebika (2017) also observed heterobeltiosis and standard heterosis for seed yield along with most of its yield components in pea which have the immense potential to exploit hybrid vigour or to isolate desirable segregants. Similar findings in pea have been reported by Nageshwar et al (2020), Katoch et al (2019), Halil et al (2019 and Kumari et al (2015).…”
Section: Resultssupporting
confidence: 89%
“…Previously, Singh et al (2019) found significant estimates of both additive (D) and dominance (H) components for all pea characters except pod length. Similar findings in pea have been reported by Katoch et al (2019), Halil and Uzun (2019), Kumari et al (2015) and Cehyan et al (2008).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The experimental material consisted of 21 genotypes, including five parental lines (Line 12, Line 13, Line 14, Line 15 and Line 17), three testers (Matar Ageta{T1}, Palam Triloki {T2} and Arkel){T3} and their 15 crosses. The parents along with the hybrids were evaluated along with one standard check; Palam Triloki in randomized block design with three replications in 2014-15 (Katoch et al,2018) with row to row and plant to plant spacing of 45 cm ( in parents 30 cm) and 10 cm respectively. Each experimental plot was of 3m x 1.8 m size accommodating 6 rows.…”
Section: Methodsmentioning
confidence: 99%
“…The hybrids' mean performance, heterosis, and potency ratio results showed a positive and substantial correlation between pod yield per plant and plant height, pod width, number of pods per plant, and pod weight, according to Galal et al (2019). However, the basis of heterosis estimated over superior parent and standard check (Palam Triloki) was explored by Katoch et al (2019). The hybrid (line 17 x Palam Triloki) displayed the highest significant and negative heterosis over the best parent for the characters, including the node at which the first flower opens, the days until 50% of the flowers have opened, and the days until the first picking, with heterotic responses of -26.09%, 5.62%, -5.66, respectively.…”
Section: Effect Of Heat Stressmentioning
confidence: 99%